Silyl Nitronate Cycloadditions Catalyzed by Cu(II)-Bisoxazoline - Dong, Li; Geng, C.; Jiao, P. (American Chemical Society, 2015)
© 2015 American Chemical Society. Cu(OTf) 2 and chiral BOX ligand-catalyzed 1,3-dipolar cycloadditions of triisopropylsilyl nitronates with a,ß-unsaturated carboximides produced chiral isoxazolines in high yields, high enantioselectivities, and complete diastereoselectivities. These chiral isoxazoline products were further converted into structurally diversified derivatives, which demonstrated the utility of the new method of constructing isoxazolines. The transition-state structure of cycloaddition was proposed in the light of the relative and absolute configurations of the products.